Kirche, Religion und Engagement in der Zivilgesellschaft Sonderauswertung des fünften Freiwilligensurveys - Sinnemann, Maria (SI-Studien aktuell, 2022)
The fifth 'Freiwilligensurvey' provides information about 20 years of civic engagement in Germany. In addition, it sets new content priorities with questions on both political culture and the field of refugees and migration. In this book, special analyses by the 'Sozialwissenschaftliches Institut der EKD' examine questions on the field of sociology of religion. They differentiate between Christian, Islamic and Christian Orthodox communities and deal intensively with the area of voluntary work in churches and religious communities. In addition to common ground, such as motivations for volunteering, it becomes clear that not all social groups have similar opportunities to access and participate in civil society.